2005
DOI: 10.1002/mrd.20411
|View full text |Cite
|
Sign up to set email alerts
|

Gradual DNA demethylation of the Oct4 promoter in cloned mouse embryos

Abstract: During differentiation, somatic cell nuclei acquire unique patterns of epigenetic modifications, such as DNA methylation, which affect the transcriptional activity of specific genes. Upon transfer into oocytes, however, the somatic nucleus undergoes reprogramming of these epigenetic modifications to achieve pluripotency. Oct4 is one of the critical pluripotency regulators, and is expressed in the germ line, including the pluripotent early embryonic cells. Previous studies showed that the upstream regulatory se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 63 publications
6
44
0
Order By: Relevance
“…3B, H3K27me3 could be clearly detected in the normal blastocyst lysates lane, whereas no H3K27me3 could be detected in the somatic cloned blastocysts lane. Similar to a previous report (27,28), Oct4 expression was much weaker in the somatic clones than the normal embryos. ␣-Tubulin was used as a control, and there was no difference in its expression between cloned and normal embryos.…”
Section: Aberrant Reprogramming Of H3k27me3 In Somatic Cellsupporting
confidence: 90%
“…3B, H3K27me3 could be clearly detected in the normal blastocyst lysates lane, whereas no H3K27me3 could be detected in the somatic cloned blastocysts lane. Similar to a previous report (27,28), Oct4 expression was much weaker in the somatic clones than the normal embryos. ␣-Tubulin was used as a control, and there was no difference in its expression between cloned and normal embryos.…”
Section: Aberrant Reprogramming Of H3k27me3 In Somatic Cellsupporting
confidence: 90%
“…In our previous study, we had analyzed the reprogramming pattern of the PE and found that this locus was completely demethylated by 48 hours postfusion (unpublished data). In mammalian cloning, the onset of Oct4 expression (visualized by Oct4-GFP fluorescence signal) coincides with the four-to eight-cell stage [4], although further demethylation of the Oct4 PP is gradual and is only comparable to that of the naturally produced embryo at the blastocyst stage [19,20]. One of the objectives of the current study was to determine whether the Oct4 PP in OG2 hybrid cells has been completely demethylated by day 2 postfusion, as is the case for the PE, or becomes gradually demethylated from the onset of Oct4-GFP reactivation onward, as is the case for reconstructed embryos.…”
Section: /Rosa26mentioning
confidence: 99%
“…Post-translational modifications have been shown to be able to modify the activity of Oct4, such as sumoylation (Wei et al, 2007) and ubiquitination (Xu et al, 2004). During the reprogramming process epigenetic marks are changed such as the removal of methyl groups on DNA (DNA demethylation) of the Oct4 promoter which has been shown during SCNT (Simonsson and Gurdon, 2004) and has also been observed in mouse (Yamazaki et al, 2006). The growth arrest and DNA damage inducible protein Gadd45a and deaminase Aid was shown to promote DNA demethylation of the Oct4 and Nanog promoters (Barreto et al, 2007;Bhutani et al, 2010).…”
Section: Molecular Mechanisms Of Reprogrammingmentioning
confidence: 99%